Proteomic Characterization of Canine Gastric Fluid by Liquid Chromatography–Mass Spectrometry for Development of Protein Biomarkers in Regurgitation, Vomiting, and Cough - Grobman, Megan; Rindt, Hansjörg; Reinero, Carol R. (Frontiers in Veterinary Science, 2021)
Reflux and aspiration in people cause and exacerbate respiratory diseases in the absence of gastrointestinal (GI) signs. Protein biomarkers in humans detect extra-esophageal reflux (EER) from oropharyngeal (OP) and bronchoalveloar lavage samples. Reflux likely contributes to respiratory disease in dogs. The objectives of this study were to analyze the canine gastric fluid (GF) proteome and compare this to the OP proteome in normal, vomiting/regurgitating and coughing dogs to identify biomarkers for EER/aspiration. Twenty-three client-owned dogs were enrolled. Canine GF samples (n=5) and OP swabs in normal (n=6), vomiting/regurgitating (n=7), and coughing (n=5) dogs were within 2 weeks of sample collection. Protein digests were analyzed by liquid chromatography mass spectrometry (LCMS). Differential abundance (DA) of proteins between groups was evaluated by Fisher Exact test with p< 0.0004 significance level after correction for multiple comparisons. DA was found between all groups (P <0.0001): GF versus normal (n=130 proteins), cough versus normal (n=22 proteins), vomiting/regurgitating versus normal (n=20 proteins). Protein abundance was highly variable between dogs. Gastrointestinal-specific proteins were found in OP swabs from vomiting/regurgitating and coughing dogs but not healthy dogs. In conclusion, the proteomic composition of the OP varies between health and disease. Presence of gastrointestinal-specific proteins in OP of coughing dogs may suggest reflux and/or aspiration as contributing factors. Variable protein abundance warrants investigation into biomarker panels.